1992
DOI: 10.2527/1992.7051509x
|View full text |Cite
|
Sign up to set email alerts
|

Disappearance of acetic acid from the bovine reticulorumen at basal and elevated concentrations of acetic acid1

Abstract: Disappearance of acetic acid was quantified to determine whether removal of this acid from the reticulorumen is altered when ruminal acetic acid concentrations are elevated. Ruminally fistulated beef steers (n = 3 per experiment; BW = 320 +/- 9 kg) were fed eight times daily a 46% corn-based concentrate:54% mixed hay diet to meet maintenance energy requirements (3.5 kg of DM/d). In situ production of acetic acid, determined by pulsed-continuous infusion of [1-14C]acetic acid, was 530 mmol/h (CV = 12%). Disappe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…This result confirms previous data obtained with the same method by Weigand et al (1972a,b), Thorlacius and Lodge (1973) and Oshio and Tahata (1984) who showed that VFA absorption rate (% of VFAs infused) was constant when their ruminal concentration increased, provided the latter was lower than 130 mM. Peters et al (1992) obtained the same result using marked VFAs. Only Dijkstra et al (1993) observed a saturation of VFA absorption when VFA concentration increased.…”
Section: Effect Of Available Vfassupporting
confidence: 91%
“…This result confirms previous data obtained with the same method by Weigand et al (1972a,b), Thorlacius and Lodge (1973) and Oshio and Tahata (1984) who showed that VFA absorption rate (% of VFAs infused) was constant when their ruminal concentration increased, provided the latter was lower than 130 mM. Peters et al (1992) obtained the same result using marked VFAs. Only Dijkstra et al (1993) observed a saturation of VFA absorption when VFA concentration increased.…”
Section: Effect Of Available Vfassupporting
confidence: 91%
“…The importance of the undisturbed metabolism of SCFA for the health and performance of ruminants can hardly be overestimated, with their production in cattle reaching more than 100 mol/day and accounting for more than 75% of the total metabolizable energy in these animals [5,8,9]. Most of the SCFA are absorbed by the ruminal epithelium [10][11][12], and although a large fraction of butyrate is metabolized intracellularly [4,[13][14][15], both in vivo [14][15][16] and in vitro studies [17][18][19][20][21] have demonstrated that considerable amounts of acetate and propionate cross the basolateral membrane of the rumen in an unmetabolized state.…”
Section: Introductionmentioning
confidence: 98%
“…VFA absorption through the rumen wall of steers represents 65 to 87% of its intraruminal production (Peters et al, 1990(Peters et al, , 1992. Considerable amounts of intraruminally produced VFA are metabolized during absorption by the rumen epithelium (Kristensen et al, 1996).…”
Section: Introductionmentioning
confidence: 99%